Are Government Transfers Efficient? An Alternative Test of the Efficient Redistribution Hypothesis - Bullock, David S. (Journal of Political Economy, 1995)
The efficient redistribution hypothesis says that no available government policies are Pareto superior to observed government policies. Efficient redistribution from government policy is a central tenet of much recent theoretical and applied political economy literature. In this paper, limitations of previous attempts to test the efficient redistribution hypothesis are discussed, and an alternative test of the efficient redistribution hypothesis that uses vector optimization theory and bootstrap methodology is presented.